Decision making for dummies - Jones, Dawna (John Wiley & Sons, 2014)
Discover the best approaches for making business decisions Today's business leaders have to face the facts?you can't separate leadership from decision making. The importance of making decisions, no matter how big or small, cannot be overstated. Decision Making For Dummies is a candid resource that helps leaders understand the impact of their choices, not only on business, but also on their credibility and reputation. Designed for managers, business owners, and anyone else who makes tough decisions on a daily basis, this guide helps you figure out if the decisions you're making are the right ones. In addition to helping you explore how to evaluate your choices, Decision Making For Dummies covers ways to receive support for decision making, delves into various decision-making styles, reviews the importance of sifting through data and information, and includes information on ways to engage others and make decisions collectively. Being in charge can be challenging, but with this guide, you don't have to go it alone. Discusses the effects of decision making and outlines the considerations that must be made to gain trust and confidence Demonstrates ways to communicate particularly sensitive decisions, and offers approaches for making bold decisions that challenge the status quo Delves into the risks and benefits of certain decisions, and shows readers the best ways to evaluate choices Outlines smart strategies for engaging others and drawing them into the decision-making process Crucial decisions need to be made every day in the business world, so there's no time to waste. Make Decision Making For Dummies your primary resource for learning to choose your actions wisely and confidently. The EPUB format of this title may not be compatible for use on all handheld devices.
Print version record
Keywords: Decision making; Economics -- Psychological aspects; Decision Making; Prise de décision; Économie politique; Aspect psychologique; decision making; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; BUSINESS & ECONOMICS; Decision-Making & Problem Solving; SELF-HELP; Personal Growth; Success; Economics; Psychological aspects